Determination Analysis of Conventional Commercial Banks on Stock Returns with EVA as a Moderating Variable - Dwi Wahyu Saputra; Sri Hermuningsih; Gendro Wiyono (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
The capital market is one indicator of a country's progress and an effective means to accelerate a country's growth when almost every country is affected by the Covid-19 virus outbreak. The purpose of the study was to determine the effect of DER, PER, LDR, and Inflation on Stock Return and also the addition of EVA as moderation. The sampling technique used a purposive sampling method with predetermined criteria and obtained 12 samples of conventional commercial banks from the annual financial statements of companies listed on the IDX during the period 2017-2021 so that the data to be processed was 60. In analyzing the data the author uses the software Eviews.9. The results of the study found that DER has no effect on Stock Return, PER has a significant positive effect on Stock Return, LDR has no significant adverse impact on Stock Return, Inflation has a significant positive effect on Stock Return, EVA is not able to moderate LDR on Stock Return, EVA is not able to moderate Inflation on Stock Return, and simultaneously DER, PER, LDR, and Inflation have an effect on Stock Return.